Property Qualities of High-Strength Heavy Concrete Made Using Recycled Asphalt Waste - Zayniddin, Nurfayziyev; Ma’ruf, Eshmo’minov (European Journal of Life Safety and Stability (2660-9630), 2023)
In this study, the authors investig ate the physical and mechanical properties of high-strength, heavy concrete in an effort to enhance the quality of concrete structures. In addition to their capillarity and pore networks, high-strength, heavy concrete with a water-to-binder ratio of 0.500 to 0.60 is often more durable than conventional concrete. Consequently, the durability-related physical and mechanical parameters of concrete sample specimens were evaluated.